EVALUATING THE THERAPEUTIC EFFECTS OF AURICULAR PRESSING COMBINED WITH ELECTROACUPUNCTURE AND SHORTWAVE THERAPY IN THE TREATMENT OF SCIATICA (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the therapeutic effects of auricular pressing combined with electroacupuncture and shortwave therapy in treating patients with sciatica due to lumbar degenerative spine.Subjects: A total of 40 patients aged 40 to 75 diagnosed with sciatica due to lumbar degenerative spine, who received treatment at the Departments of Surgery and Rehabilitation of the Lao Cai Provincial Traditional Medicine Hospital from July 2025 to March 2026.Research method: A clinical interventional study comparing outcomes before and after treatment.Results: After 14 days of treatment, the mean VAS score decreased from 4.63 ± 1.01 to 2.23 ± 0.92; the mean Schöber index improved from 11.52 ± 0.73 cm to 13.55 ± 0.51 cm; the mean Lasègue angle increased from 58.63 ± 7.680 to 70.18 ± 5.070; and the mean ODI score decreased from 8.85 ± 2.16 to 4.73 ± 1.63. All improvements were statistically significant with p < 0.05.Conclusion: The combination of auricular pressing, electroacupuncture, and shortwave therapy effectively reduces pain and improves ODI score in patients with sciatica caused by lumbar degenerative spine.